2005
DOI: 10.1111/j.1468-2508.2005.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Where Turnout Matters: The Consequences of Uneven Turnout in City Politics

Abstract: There is a widespread concern that imbalances in voter turnout across race and class have led to biased outcomes in American democracy. Yet empirical tests have generally found that the unrepresentative nature of the electorate has little effect on who wins and loses elections. We challenge this finding by arguing that existing research minimizes the chances of finding bias because it focuses largely on national elections where turnout is relatively high and where minority groups are generally too small a perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(122 citation statements)
references
References 27 publications
3
117
0
2
Order By: Relevance
“…However, they noted that, controlling for socio-economic factors and citizenship, Hispanics are not associated with lower rates of turnout in California municipal elections. Finally, Hajnal and Trounstine (2005) found that lower turnout rates at the local level leads to political underrepresentation, particularly for Asian Americans and Latinos.…”
Section: Voter Turnout In American Local Electionsmentioning
confidence: 96%
“…However, they noted that, controlling for socio-economic factors and citizenship, Hispanics are not associated with lower rates of turnout in California municipal elections. Finally, Hajnal and Trounstine (2005) found that lower turnout rates at the local level leads to political underrepresentation, particularly for Asian Americans and Latinos.…”
Section: Voter Turnout In American Local Electionsmentioning
confidence: 96%
“…In fact, Hajnal and Trounstine (2005) argue that the skew of representation resulting from uneven participation is likely to be more severe in elections in which overall rates of turnout are exceedingly low such as low salience municipal elections. Through a series of simulations, Hajnal and Trounstine (2005) uncover a number of instances in which higher rates of turnout among urban ethnic minority groups would have influenced the outcome of municipal elections. The different ethnic and ideological orientations of representatives in the counterfactual scenarios Hajnal and Trounstine (2005) examine likely would have impacted local policy outcomes.…”
Section: Voter Turnout Among the Urban Poormentioning
confidence: 97%
“…Through a series of simulations, Hajnal and Trounstine (2005) uncover a number of instances in which higher rates of turnout among urban ethnic minority groups would have influenced the outcome of municipal elections. The different ethnic and ideological orientations of representatives in the counterfactual scenarios Hajnal and Trounstine (2005) examine likely would have impacted local policy outcomes. In many ways, the composition of chambers of government, particularly at the local level, can have an effect upon the quality and availability of public assistance programs such as public housing.…”
Section: Voter Turnout Among the Urban Poormentioning
confidence: 99%
“…From their point of view, turnout level can truly suggest "who wins and loses" (cf. Hajnal and Trounstine 2005). The study of Pacek and Radcliff (1995), inspired by the pathbreaking work of DeNardo (1980), is seminal in this respect.…”
Section: Theories Of the Effect Of Voter Turnout On The Gains Of Indimentioning
confidence: 98%